Postcoital bleeding due to cervical endometriosis - Seval, Mehmet Murat (BMJ Publishing Group, 2013)
Endometriosis of the uterine cervix is a rare lesion that is generally asymptomatic in gynaecological practice. We present a case with postcoital bleeding due to a cervical mass mimicking cervical polyp or fibroma which was histologically proven as cervical endometriosis later. Cervical endometriosis should be considered in the differential diagnosis of cervical masses with postcoital bleeding.